A comparative survey on potentially futile treatments between Japanese nurses and laypeople. (February 2014) - Kadooka, Yasuhiro; Asai, Atushi; Fukuyama, Miki; Bito, Seiji
In the issue of futile treatments, patients and healthcare professionals tend to disagree. We conducted an Internet questionnaire survey and explored the Japanese nurses' attitude toward this topic, comparing with that of laypeople. In total, 522 nurses and 1134 laypeople completed the questionnaire. Nurse respondents were significantly less in favor of providing potentially futile treatments in hypothetical vignettes and stressed quality of life of the patient for judging the futility of a certain treatment. Of them, 85.4% reported having experienced providing such treatments. Reasons for providing them included factors related to not only patients but also healthcare teams. Our results indicate that attitudes among Japanese nurses toward the issue of futile treatments are different from patients and that their actual practice is influenced by several situational factors.